2023
DOI: 10.1177/03635465231159899
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Distribution of Bone Bruise Patterns in Contact and Noncontact Acute Anterior Cruciate Ligament Injuries

Abstract: Background: Bone bruises are commonly seen on magnetic resonance imaging (MRI) in acute anterior cruciate ligament (ACL) injuries and can provide insight into the underlying mechanism of injury. There are limited reports that have compared the bone bruise patterns between contact and noncontact mechanisms of ACL injury. Purpose: To examine and compare the number and location of bone bruises in contact and noncontact ACL injuries. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Three hundred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Our study not only recorded the bone bruise but also calculate the specific location of bone bruises of ACL rupture and patellar dislocation (Fig 6). For non-contact sports knee injury, bone bruise is not only an intensity signal, but also a footprint of damaging process, which could be as implications of injury mechanism, or the product of the mechanism since different mechanisms of injury have different bone bruise patterns 25 . Numerical optimization was used to maximize overlap of the bone bruises on the femur and tibia and to predict the position of injury by Kim Sophia Y, at al who choose the most commonly 3-and 4-bone bruise of ACL rupture as Infrastructure to create 3-dimensional surface models, and found landing on an extended knee is a high risk for ACL injury 15,17 while others found that knee valgus is the critical component of the injury mechanism 12,19,26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study not only recorded the bone bruise but also calculate the specific location of bone bruises of ACL rupture and patellar dislocation (Fig 6). For non-contact sports knee injury, bone bruise is not only an intensity signal, but also a footprint of damaging process, which could be as implications of injury mechanism, or the product of the mechanism since different mechanisms of injury have different bone bruise patterns 25 . Numerical optimization was used to maximize overlap of the bone bruises on the femur and tibia and to predict the position of injury by Kim Sophia Y, at al who choose the most commonly 3-and 4-bone bruise of ACL rupture as Infrastructure to create 3-dimensional surface models, and found landing on an extended knee is a high risk for ACL injury 15,17 while others found that knee valgus is the critical component of the injury mechanism 12,19,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown that bone bruises of the knee on MRI could provide implications for the mechanism of ACL and patellar dislocation injury 20,35,37 . In addition, the bone bruise patterns of femur and tibia in ACL injury differed with the femur and patella bone bruises in patellar dislocation 25,41 , and there are actually limited reports that have compared the bone bruise patterns between different knee injury.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors identified an association between BB distribution and injury mechanism, e.g., non-contact valgus injuries represented by BB predominantly in the LTP and LFC [ 3 , 9 , 34 , 45 47 ]. Other authors found medial BB representative of extension and anterior tibial translation mechanisms [ 37 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The occult fractures described in these studies were primarily of the bone bruise type, sometimes referred to as nondisplaced fractures. Their typical localization in the anterior to middle segment of the lateral femoral condyle (LFC) and the middle to posterior segment of the lateral tibial plateau (LTP) reflects the mechanism of injury to the ACL, in which the lateral tibial plateau subluxates anteriorly, resulting in a violent collision between the anterolateral aspect of the LFC and the posterolateral area of the tibial plateau (PLTP) [7, 8, 12, 22, 31, 40].…”
Section: Introductionmentioning
confidence: 99%